Company Supply Chain Management Performance Seen from The Aspect of Information Sharing and Cooperation (Empirical Study of MSMEs in the Food Industry Sector in Kertajati Regency) - Deni Istiono; Nining Kurniasih; Pupung Pamungkas (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
The small food processing industry is an industrial sector that is quite capable of surviving economic shocks, because every year the need for food increases along with increasing population growth. Small and medium industries have an important role in developing processing businesses, especially in the food sector. The Kertajati specialty processed food industry is an industry that has potential to be developed, because each region has its own characteristics and characteristics. Suppliers, manufacturers, distributors, retailers and customers work together in the product creation process through to product distribution to final consumers, giving birth to the concept of supply chain management. This research aims to analyze the influence of information sharing and cooperation on the performance of supply chain management of MSMEs in the Food Industry Sector in the Kertajati District Region, both partially and simultaneously. The population in this research is small and medium industries in Kertajati District, Majalengka Regency which are engaged in processed food production, totaling 92 MSMEs. The sample used 48 MSMEs as respondents from the entire population, by collecting data through questionnaires. The sampling technique in this research uses probability sampling with a simple random sampling method. The type and source of data used is primary. The analysis technique used is correlation, where previously an instrument test was carried out using validity and reliability tests, then data transformation and data normality test, then hypothesis testing was carried out partially with the t test and simultaneously with the F test operated through the SPSS 21 program. The results of this research show that partially information sharing and cooperation have a significant effect on supply chain management performance. Simultaneous testing shows that information sharing and cooperation have a significant effect on supply chain management performance.